1993
DOI: 10.1128/jcm.31.11.3013-3016.1993
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Chlamydia trachomatis urethritis in men by polymerase chain reaction assay of first-catch urine

Abstract: To determine the accuracy of a recently developed polymerase chain reaction (PCR) urine assay to detect Chiamydia trachomatis urethral infection in men, we obtained urethral swabs and first-catch urine from 365 men attending a sexually transmitted diseases clinic. Thirty-three (91%Y) of the 365 men were infected with C. trachomatis as defined by urethral culture. Thirty-two of the 33 men with culture-positive urethral swabs also had PCR-positive urine assays. Of 332 patients with culture-negative urethral swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
2

Year Published

1994
1994
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 28 publications
2
36
2
Order By: Relevance
“…7,8 The presence of DNA polymerase inhibitors was first described in endocervical specimens, where the ensuing percentage of false negative results varied between 4% and 10% in different reports, depending on the prevalence of chlamydial infection in the population studied. 4,5 PCR inhibitors were also found in male urine although they were first thought to occur less frequently than in endocervical specimens, i.e., in 0-3% of true positive specimens. 3,4 Wiesenfeld et al 14 reported the presence of PCR inhibitors in almost 10% of positive male urine specimens in a high-risk population with 17% incidence of chlamydial infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,8 The presence of DNA polymerase inhibitors was first described in endocervical specimens, where the ensuing percentage of false negative results varied between 4% and 10% in different reports, depending on the prevalence of chlamydial infection in the population studied. 4,5 PCR inhibitors were also found in male urine although they were first thought to occur less frequently than in endocervical specimens, i.e., in 0-3% of true positive specimens. 3,4 Wiesenfeld et al 14 reported the presence of PCR inhibitors in almost 10% of positive male urine specimens in a high-risk population with 17% incidence of chlamydial infection.…”
Section: Discussionmentioning
confidence: 99%
“…PCR on male urine specimens has been shown to be a highly sensitive and specific non-invasive technique for the diagnosis of C. trachomatis, providing an opportunity for the identification of both asymptomatic and symptomatic infected patients. 3,4 According to recent studies, the amplification power of PCR appears to make possible the same approach in females as well. 7,8 The presence of DNA polymerase inhibitors was first described in endocervical specimens, where the ensuing percentage of false negative results varied between 4% and 10% in different reports, depending on the prevalence of chlamydial infection in the population studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies using either cervical swabs, urethral swabs from females or males, or urine specimens from males, the Amplieor PCR assay was more sensitive than the reference methods used, such as the cell culture method, the Chlamydiazyme assay or the Gen-Probe PACE 2 assay [36,[38][39][40][41][42][43][44][45][46]. In one study using cervical spec-imens, the observed sensitivity of the Amplieor PCR assay was lower than that of the cell culture method [47].…”
Section: Commercially Available Amplieor Pcr Assaymentioning
confidence: 99%